2021
DOI: 10.1152/japplphysiol.00464.2021
|View full text |Cite
|
Sign up to set email alerts
|

Acute cellular and molecular responses and chronic adaptations to low-load blood flow restriction and high-load resistance exercise in trained individuals

Abstract: Blood flow restriction (BFR) with low-load resistance exercise (RE) is often used as a surrogate to traditional high-load RE to stimulate muscular adaptations, such as hypertrophy and strength. However, it is not clear whether such adaptations are achieved through similar cellular and molecular processes. We compared changes in muscle function, morphology and signaling pathways between these differing training protocols. Twenty-one males and females (mean ± SD: 24.3 ± 3.1 years) experienced with resistance tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Davids et al, compared changes in muscle function, morphology and signaling pathways in twenty-one subjects who performed LIBFR or over the course of 9-weeks. 5 In this study it was found that muscle strength was superior in the HIRT group as expected given the specificity of training. However, acute phosphorylation of key proteins involved in hypertrophic pathways as well as expression of ribosomal RNA transcription factors were relatively comparable between the groups, suggesting the mechanisms for hypertrophy may be stimulated by LIRT when augmented with BFR.…”
Section: Molecular and Cellularsupporting
confidence: 65%
See 2 more Smart Citations
“…Davids et al, compared changes in muscle function, morphology and signaling pathways in twenty-one subjects who performed LIBFR or over the course of 9-weeks. 5 In this study it was found that muscle strength was superior in the HIRT group as expected given the specificity of training. However, acute phosphorylation of key proteins involved in hypertrophic pathways as well as expression of ribosomal RNA transcription factors were relatively comparable between the groups, suggesting the mechanisms for hypertrophy may be stimulated by LIRT when augmented with BFR.…”
Section: Molecular and Cellularsupporting
confidence: 65%
“…A body of evidence suggests that low intensity resistance training (LIRT) with BFR (LIBFR) has the ability to produce hypertrophy based outcomes that exceed LIRT without BFR, and are similar to moderate to high intensity resistance training (MHIRT). [5][6][7] Explanations for these outcomes likely reside in the molecular and cellular benefits of applying a BFR tourniquet during training, which by way of a hypoxic effect and the accumulation of metabolites and cell swelling mimics a high intensity environment. While MHIRT possesses a specificity to sports or activities that require greater muscle activation that lower intensity training does not, it is clear that adding LIBFR is a desirable option for those individuals with a low exercise tolerance such as patient populations and those undergoing surgical and orthobiologic procedures.…”
Section: Molecular and Cellularmentioning
confidence: 99%
See 1 more Smart Citation
“…Two micrograms of isolated RNA were reverse transcribed using iScript cDNA synthesis kit (Bio-Rad Laboratories) to produce 20 μL of complementary DNA (cDNA) for gene expression analysis. After performing standard curves from pooled cDNA, as recently described, 32,33 the cDNA was diluted 1:5 for most gene targets, but for 45 S pre-rRNA, c-MYC, POL1RA and TAF-1A the cDNA was diluted 1:25.…”
Section: Reverse Transcriptionmentioning
confidence: 99%
“…As well, blood flow restriction combined with endurance training has also been shown to improve cardiopulmonary health ( Conceição and Ugrinowitsch, 2019 ). Furthermore, BFRT can effectively improve muscle mass and strength in different populations ( Davids et al, 2021 ; Korkmaz et al, 2022 ), improve muscle fitness ( Hill et al, 2021 ), increase aerobic capacity ( Billaut et al, 2022 ), promote knee rehabilitation ( Centner et al, 2019 ), stimulate acute bone formation markers and hormonal responses ( Bemben et al, 2022 ), and improve athletic performance thereby maintaining overall good health ( Wortman et al, 2021 ). However, in the field of BFRT intervention for overweight/obesity, studies on anthropometric indicators and blood lipids have shown different results ( Da Silva et al, 2020 ; Kim and LeeDongminWon, 2021 ; Mohammadiyan et al, 2021 ; Yong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%